Menciptakan Kreativitas Usaha Oleh Siswa/Siswi Dengan Produk Unik Berbasis Iptek - Septi Anggela; Desi Ulandari; Givani Anatasya; Veta Lidya Delimah Pasaribu (CV. ITTC INDONESIA, 2025)
Developing creativity and an entrepreneurial spirit in high school students is an urgent need to prepare a young generation capable of competing in the digital era. However, the lack of understanding of the integration of Science and Technology (IPTEK) in business product development is a major constraint. This Community Service (PKM) activity aims to enhance the creativity and entrepreneurial skills of 10th-grade students of Pelita Bangsa High School through the development of science and technology-based products. (PKM) conducted by Pamulang University students aims to motivate and encourage students to produce creative and innovative work as a provision for future entrepreneurship, develop students' creativity and abilities in creating products with added value and solutions based on the use of science and technology, provide applicable and engaging teaching materials for 10th-grade students to improve their technology-based entrepreneurial skills and knowledge. This activity is expected to not only provide short-term solutions but also build the foundation of Pelita Bangsa High School students.The implementation method uses a participatory approach, a question and answer session. The results of the activity show a significant increase in participants' understanding of the concept of science and technology-based entrepreneurship, with 85% of participants being able to produce innovative product ideas that integrate simple technology. This activity not only provides theoretical knowledge but also triggers the emergence of creative business ideas that can be developed further.